PENGARUH DEVIDEND PER SHARE (DPS), RETURN ON EQUITY (ROE) DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM (Studi Empiris Pada Perusahaan Infrastruktur, Utilitas dan Transportasi Yang Terdaftar Di BEI Periode 2012-2015) (UNIVERSITAS ISLAM MALANG, 2017)
This research aims to know the effect of the Dividend per Share on stock price, Return on Equity effect on stock price and the Net Profit Margin on stock price. This research is a quantitative study using secondary data such as financial statements. The sample used is a company engaged in the sectors of Infrastructure, Utilities and Transportation listed on BEI for the period 20122015. The sample in this study using purposive sampling a total of 11 companies. While the method of data analysis used in this research is multiple linear regression analysis. The results of this study indicate that the dividend per share (DPS) have a significant effect on stock prices. While Return on Equity (ROE) and Net Profit Margin (NPM) had no significant effect on stock prices.